Language of Propaganda in The Great Hack Movie (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
The mass media opposed Donald Trump for his victory as president in the 2016 U.S election because he was considered involved in exploiting voters’ personal data. This issue was narrated in “The Great Hack” movie. This study attempted to scrutinize propaganda message potential through linguistic and non-linguistic (visual) components in that movie and investigate how both types of components interplayed to create the intended message. The analysis was presented across two axes. First, by using Halliday and Matthiessen’s Systemic Functional Linguistics (SFL), the study primarily focused on the propaganda messages constructed through words, phrases, and clauses. The visual components were analyzed in the second step as complementary analysis. The study found that “The Great Hack” movie wants to construct realities that Donald Trump unfairly gained a victory for the election with Hillary Clinton as a deliberately weakened candidate. In addition, the linguistic and visual components have relations to reinforce and elaborate the intended messages.